2020
DOI: 10.1128/aem.02838-19
|View full text |Cite
|
Sign up to set email alerts
|

Sml1 Inhibits the DNA Repair Activity of Rev1 in Saccharomyces cerevisiae during Oxidative Stress

Abstract: In Saccharomyces cerevisiae, Y family DNA polymerase Rev1 is involved in the repair of DNA damage by translesion DNA synthesis (TLS). In the current study, to elucidate the role of Rev1 in oxidative stress-induced DNA damage in S. cerevisiae, REV1 was deleted and overexpressed; transcriptome analysis of these mutants along with the wild-type strain was performed to screen potential genes that could be associated with REV1 during response to DNA damage. When the yeast cells were treated with 2 mM H2O2, the dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
(50 reference statements)
0
9
1
Order By: Relevance
“…DNA damage can also result in mutations and genomic instability without efficient repair, which underlies the malignant transformation of cells. Interestingly, emerging evidence has revealed that ROS/RNS can disrupt DNA repair pathways, including base excision repair (BER), direct reversal, and double-strand break repair [142,[172][173][174]. Patients with cancer exhibit lower BER efficiency than healthy participants, partially due to the ROS-dependent inhibition of DNA repair enzymes.…”
Section: Ros Drives Inflammation-induced Genomic Instabilitymentioning
confidence: 99%
“…DNA damage can also result in mutations and genomic instability without efficient repair, which underlies the malignant transformation of cells. Interestingly, emerging evidence has revealed that ROS/RNS can disrupt DNA repair pathways, including base excision repair (BER), direct reversal, and double-strand break repair [142,[172][173][174]. Patients with cancer exhibit lower BER efficiency than healthy participants, partially due to the ROS-dependent inhibition of DNA repair enzymes.…”
Section: Ros Drives Inflammation-induced Genomic Instabilitymentioning
confidence: 99%
“…We confirm and quantify C. albicans DNA damage in the presence of antifungal drugs, and further find that numerous predicted error-prone polymerases (and related factors) are upregulated in the presence of DNA-damaging agents, including antifungal drugs. We further focus on REV1, which when deleted, leads to an increased mutation rate (in opposition to what is observed in S. cerevisiae [43][44][45] ), and a corresponding increase in evolved resistance to the antifungal drug caspofungin. Deletion of REV1 also causes a higher abundance of the protein Shm1, which is also involved in the C. albicans mutation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, recent studies have confirmed the important role of REV1 in DNA damage repair and the maintenance of genomic stability. In saccharomyces cerevisiae, cells lacking REV1 are sensitive to DNA damage agents, including cisplatin, mitomycin C and UV radiation [ 7 ]. Similarly, REV1 was found to play an important role in the activation of the ATR-Chk1 checkpoint during mitomycin C-induced interstrand crosslink repair in African clawed toad egg extracts [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated REV1 expression enhances cellular tolerance to UV damage. High levels of REV1 can increase the frequency of gene mutations in cells, thus helping them to adapt to environmental stress [ 7 , 9 , 10 ]. Radiotherapy is a cytotoxic therapy that exerts its therapeutic effect mainly by inducing double-stranded DNA breaks in tumor cells, and DNA damage repair is an important factor affecting tumor radiosensitivity [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%